2015
DOI: 10.1016/j.powtec.2015.04.039
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the dynamics of the FT4 powder rheometer

Abstract: a b s t r a c t a r t i c l e i n f o Available online xxxx Keywords: Flowability Dynamic flow Powder rheology DEM Shear stressTraditional powder flow measurement devices, such as shear cells, operate in the quasi-static regime of shear strain rate. The FT4 powder rheometer of Freeman Technology, developed over the last two decades, has provided a clearer differentiation of powder flowability in some instances. This has been attributed to the instrument operating in the dynamic regime of shear strain rates, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 17 publications
2
52
0
Order By: Relevance
“…It was observed that the flow energy could decrease to 12 mJ if the particle-particle friction coefficient was set to zero. Bharadwaj et al (2010) and Hare et al (2015) also showed that the flow energy was sensitive to the interparticle friction coefficient. Hence, to get a better agreement, it is possible to fine-tune the friction coefficients so that the flow energy is the same in both experimental work and numerical simulation.…”
Section: Snapshotsmentioning
confidence: 97%
See 3 more Smart Citations
“…It was observed that the flow energy could decrease to 12 mJ if the particle-particle friction coefficient was set to zero. Bharadwaj et al (2010) and Hare et al (2015) also showed that the flow energy was sensitive to the interparticle friction coefficient. Hence, to get a better agreement, it is possible to fine-tune the friction coefficients so that the flow energy is the same in both experimental work and numerical simulation.…”
Section: Snapshotsmentioning
confidence: 97%
“…Hence, to get a better agreement, it is possible to fine-tune the friction coefficients so that the flow energy is the same in both experimental work and numerical simulation. This approach has been adopted by Hare et al (2015) in simulating the dynamics of cohesive particles in FT4 rheometer.…”
Section: Snapshotsmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear elastic-plastic and adhesive contact model of Pasha et al [3] is used to represent cohesive spheres with a surface energy of 29 mJ/m 2 , in order to correlate with the experimental work of Hare et al [4]. The particle-particle sliding and rolling friction coefficients are set at 0.3 and 0.01, respectively, to best represent the experimental glass beads in their work.…”
Section: Stress Analysismentioning
confidence: 99%